Chitosan-g-poly(acrylic acid-co-acrylonitrile) Hydrogels with Potential Biomedical Applications as Drug Delivery Systems - Sadeghi, Mohammad; Mohammadinasab, Esmat; Yarahmadi, Mojgan (Asian Journal of Chemistry, 2012)
In this work, acrylonitrile and acrylic acid monomers were directly grafted onto chitosan using ammonium persulfate as an initiator and methylenebisacrylamide as a crosslinking agent under an inert atmosphere. A mechanism for hydrogel formation was proposed and the structure of the product was established using FTIR spectroscopy. The chitosan-g-poly(acrylic acid-co-acrylonitrile) hydrogel exhibited a pH-responsive swelling-deswelling behaviour at pH's 2 and 8. This on-off switching behaviour provides the hydrogel with the potential to control delivery of bioactive agents. Release profiles of metronidozule drug, from the hydrogels were studied under both simulated gastric and intestinal pH conditions.